2017
DOI: 10.1021/acs.orglett.7b01821
|View full text |Cite
|
Sign up to set email alerts
|

Chemo- and Stereoselective Crotylation of Aldehydes and Cyclic Aldimines with Allylic gem-Diboronate Ester

Abstract: We report a highly chemo- and stereoselective crotylation of aldehydes and cyclic aldimines with allylic-gem-diboronate ester as a new type of organoboron reagent. The allylic-gem-diboronate ester undergoes the crotylation with aldehydes and cyclic aldimines in excellent stereoselectivity, forming anti-5,6-disubstituted oxaborinin-2-ols or (E)-δ-boryl-anti-homoallylic amines in high efficiency. The reaction shows a wide range of substrate scope and excellent functional group tolerance. The synthetic applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…The synthesis and reactivity of allylic gem-bis[( pinacolato)boryl]alkanes were initially reported by the Cho group. 39 They reported a successful racemic crotylation of aldehydes and cyclic aldimines using allylic gem-bis[( pinacolato)boryl] alkanes. In 2020, the Meek group reported the addition of a boron-stabilized chiral allylic copper species to a variety of aryl aldimines, 40 generating enantioenriched homoallylic amines 60 (Scheme 10a).…”
Section: Cu-catalyzed Transformations Of Gem-diborylalkanesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis and reactivity of allylic gem-bis[( pinacolato)boryl]alkanes were initially reported by the Cho group. 39 They reported a successful racemic crotylation of aldehydes and cyclic aldimines using allylic gem-bis[( pinacolato)boryl] alkanes. In 2020, the Meek group reported the addition of a boron-stabilized chiral allylic copper species to a variety of aryl aldimines, 40 generating enantioenriched homoallylic amines 60 (Scheme 10a).…”
Section: Cu-catalyzed Transformations Of Gem-diborylalkanesmentioning
confidence: 99%
“…In the same year, the Cho group reported another protocol for the enantioselective allyl transfer of aldehydes using the allylic gem-diboronate ester (Scheme 18a). 57 The reaction engaged (R)-TRIP catalysis proceeds through the intermediate 99. Chen and his group later extended the enantioselective functionalization of α,α-disubstituted crotylboronate reagents 100 with an aldehyde in the presence of chiral phosphoric acid (Scheme 18b).…”
Section: Transition Metal-free Functionalization Of Gem-diborylalkanesmentioning
confidence: 99%
“…Cho and co‐workers reported that allylic‐ gem ‐diboronates undergo the crotylation with cyclic aldimines forming ( E )‐δ‐boryl‐ anti ‐homoallylic amines in high efficiency, despite the fact that copper(I) complexes were not catalyzing the reaction [19] . However, Meek and co‐workers found that a (phosphoramidite)‐Cu complex facilitates the catalytic reaction between allyldiboronates and aldimines towards the enantio‐ and diastereoselective formation of homoallylic amines.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Cho et al reported the diastereoselective addition of isolated allyldiboron ester 5 to a variety of cyclic sulfonyl imines, although the report is limited to the E -crotyl reagent (eq ). …”
mentioning
confidence: 99%